2007
DOI: 10.1155/2008/176275
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Peroxisome Proliferator‐Activated Receptors, Adenosine Monophosphate‐Activated Kinase, and Adiponectin in the Ovary

Abstract: The mechanisms controlling the interaction between energy balance and reproduction are the subject of intensive investigations. The integrated control of these systems is probably a multifaceted phenomenon involving an array of signals governing energy homeostasis, metabolism, and fertility. Two fuel sensors, PPARs, a superfamily of nuclear receptors and the kinase AMPK, integrate energy control and lipid and glucose homeostasis. Adiponectin, one of the adipocyte-derived factors mediate its actions through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 90 publications
0
61
1
Order By: Relevance
“…This conclusion is also supported by the absence of AMPK activation in chicken brain, liver, or skeletal muscle in response to a 24-h fast; AMPK was, however, activated in muscle after a 48-h fast (Proszkowiec-Weglarz et al 2006). In contrast, in the ovary of several species, including hen, AMPK activity varies during follicle development, independently of nutrition level (Dupont et al 2008). In the present study, it was of interest to investigate whether the expression of some genes and proteins, known as insulin sensitive in mammals, had been altered in the liver or the muscle following insulin privation (5hrfed-Ab).…”
Section: Discussionmentioning
confidence: 77%
“…This conclusion is also supported by the absence of AMPK activation in chicken brain, liver, or skeletal muscle in response to a 24-h fast; AMPK was, however, activated in muscle after a 48-h fast (Proszkowiec-Weglarz et al 2006). In contrast, in the ovary of several species, including hen, AMPK activity varies during follicle development, independently of nutrition level (Dupont et al 2008). In the present study, it was of interest to investigate whether the expression of some genes and proteins, known as insulin sensitive in mammals, had been altered in the liver or the muscle following insulin privation (5hrfed-Ab).…”
Section: Discussionmentioning
confidence: 77%
“…Many studies have shown that PPARs gene and/or protein expression varies depending on ovarian cell type, physiological status and the species [14,[22][23][24][25][26]. It has also been frequently reported that PPARs are engaged in the regulation of various ovarian functions.…”
Section: Ppars In the Ovarymentioning
confidence: 99%
“…Although not all known PKs are demonstrated in the ovary, presence of members of MAPK, CDK, TK, PI3K, Akt, PKA, AK, HER kinases, mTOR and activin receptor like kinase (ALK) families in ovarian follicular granulosa cells has been well documented (Sirotkin et al, 2000a(Sirotkin et al, , 2004Shimada et al, 2001;Makarevich et al, 2002Makarevich et al, , 2004bHunzicker-Dunn and Maizels, 2006;Kumar et al, 2007;Sawada et al, 2007;Wang and Tsang, 2007;Dupont et al, 2008). Furthermore, observations of effects of activators and blockers of PKs indicate presence and importance of a number of other PKs in control of ovarian functions and in mediating effect of hormones on these functions (see below).…”
Section: Presence Of Protein Kinases In the Ovarymentioning
confidence: 99%
“…Despite the importance of PKs, the reviews concerning ovarian PKs published previously are focused on one PK (protein kinase A- Dupont, 2008, Aurora kinase- Macarulla et al, 2008) or particular group of PKs (Ca2þ-dependent PKs- Ducibella and Fissore, 2008), one ovarian structure (oocyte- Brunet and Maro, 2005;Dekel, 2005;Kimura et al, 2007; Corpus luteum -Diaz et al, 2002;Meidan et al, 2005;Gadsby et al, 2006), particular process (oogenesis- Brunet and Maro, 2005;Dekel, 2005;Kimura et al, 2007, cancerogenesis-Kamath andBuolamwini, 2006;Martin and Schilder, 2006;Markman, 2008) or hormone (FSH-Hillier, 2001;Richards et al, 2002;Hunzicker-Dunn and Maizels, 2006;Dupont et al, 2008). To our knowledge, no attempts to put together available data concerning involvement of different known PKs in control of different ovarian processes have been previously made.…”
mentioning
confidence: 99%